Hybrid Polariton Devices: Ultrafast Response of a Hybrid Device Based on Strongly Coupled Monolayer WS2 and Photonic Crystals: The Effect of Photoinduced Coulombic Screening (Laser Photonics Rev. 14(4)/2020). Issue 4 (9th April 2020) - Tang, Yuxiang; Zhang, Yanbin; Ouyang, Hao; Zhao, Maoxiong; Hao, Hao; Wei, Ke; Li, Han; Sui, Yizhen; You, Jie; Zheng, Xin; Xu, Zhongjie; Cheng, Xiangai; et al.
Abstract : In article number 1900419, Lei Shi, Tian Jiang, and co‐workers fabricate a hybrid polariton device in which strong coupling interactions occur between a photonic crystal (PhC) slab and monolayer tungsten disulfide (WS2 ). Moreover, transient dynamics studies show that the nonequilibrium coulombic screening effect in WS2 can explicitly influence the ultrafast response of this polariton device. These results are expected to deepen the understanding of photophysics in polariton and permit the active tunability of light‐matter interactions.